Sedimentology of a Permian playa lake: the Boda Claystone Formation, Hungary - Konrád, Gyula; Sebe, Krisztina; Halász, Amadé; Babinszki, Ilyenkov (Geologos, 2010)
The Upper Permian Boda Claystone Formation (BCF) in SW Hungary has been previously been identiﬁed as a saline lake deposit. A country-wide screening found this 800–1000 m thick succession the most suitable for the disposal of high-level radioactive waste in Hungary, and research into this formation has consequently been intensiﬁed since. The investigations included a detailed study of the sedimentological characteristics. Data obtained by mapping of the 25 km2 outcrop area of the formation and from more than 40 boreholes were processed. The sedimentary structures were investigated on outcrop to microscopic scales, and cycles in the succession were interpreted. The main lithofacies, sedimentary structures and ichnofossils are presented. They indicate that the major part of the succession was deposited in a playa mudﬂat and is not of lacustrine origin in a strict sense. The lake sediments are re-presented by laminated and ripple-marked/ﬂaser-type cross-laminated claystones and siltstones and by massive dolo-mites; trace fossils include crawling traces and burrows. Partial or complete drying out of the lake commonly occurred after the formation of carbonate mud by evaporation. Periodic ﬂuvial inﬂux is recorded by cross-bedded sandstones and unsorted gravelly sandstones of up to pebble-sized angular grains. Fenestral and stromatolitic structures reﬂect the repeated appearance of playa mudﬂat conditions. The silty claystones, which compose the major part of the succession, lost their primary structures due to pedogenic processes and indicate prolonged subaerial intervals with soil formation and only ephemeral inundations. The presence of pedogenic carbonate concretions supports the interpretation of an arid climate and a relatively shallow groundwater table. Drying-out events shown by desiccation cracks and authigenic breccias can be traced all over the succession. The various facies form small-scale sedimentary cycles showing a shallowing-upward trend and the growing inﬂuence of aridity and subaerial exposure.